2011
DOI: 10.1002/fut.20544
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Hedge Horizon on Optimal Hedge Size and Effectiveness When Prices are Cointegrated

Abstract: This study compares two alternative regression specifications for sizing hedge positions and measuring hedge effectiveness: a simple regression on price changes and an error correction model (ECM). We show that, when the prices of the hedged item and the hedging instrument are cointegrated, both specifications yield similar results which depend on the hedge horizon (i.e., the time frame for measuring price changes). In particular, the estimated hedge ratio and regression R 2 will both be small when price chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 56 publications
1
36
0
2
Order By: Relevance
“…Time varying hedge ratio assumes the spot price volatility have a changing correlation, that varies over time, with price volatility futures. Assumptions of time varying hedge ratio is pretty much supported by previous research as showed by Cotter and Hanly (2012) and Juhl et al (2012). However, the implementation of time varying hedge ratio requires higher cost because hedge ratio can vary over time reflecting correlation of spot and futures price volatility.…”
Section: Jurnal Ekonomimentioning
confidence: 83%
See 3 more Smart Citations
“…Time varying hedge ratio assumes the spot price volatility have a changing correlation, that varies over time, with price volatility futures. Assumptions of time varying hedge ratio is pretty much supported by previous research as showed by Cotter and Hanly (2012) and Juhl et al (2012). However, the implementation of time varying hedge ratio requires higher cost because hedge ratio can vary over time reflecting correlation of spot and futures price volatility.…”
Section: Jurnal Ekonomimentioning
confidence: 83%
“…It is found also by Gupta and Kaur (2015) in India, Bhargava and Malhotra (2007) in some Asian countries, and Lien (2005) in the United States and some European countries. Juhl et al, (2012) show the effectiveness of hedging strategy in the short term by using simpler method is higher than using the more complex method. Some researchers suggest that the effectiveness of hedging strategy is not only influenced by appropriate hedge ratio measurement method but also affected by market liquidity conditions (Gupta and Singh, 2009) and asymmetric behavior of spot and futures price volatility (Cotter and Hanly, 2012).…”
Section: Jurnal Ekonomimentioning
confidence: 89%
See 2 more Smart Citations
“…We estimate and compare optimal utility based hedges using performance metrics based on the underlying optimization criteria as well as an economic comparison between the different hedging models using Value at Risk (VaR). Given the potential impact of hedge horizon on optimal hedges (see Juhl, Kawaller and Koch, 2012) we estimate hedge strategies across three time horizons, daily, weekly and monthly. For our analysis we use two of the most broadly used characterisations of investor utility; quadratic and exponential.…”
Section: Introductionmentioning
confidence: 99%